PENGUATAN MOTIVASI DAN KETERAMPILAN MENULIS KARYA ANTOLOGI PADA TENAGA PERPUSTAKAAN UIN GUSDUR PEKALONGAN - Arditya Prayogi; Khusnu Asirah; Qurrota A'yun; Nurul Maisyal (Universitas Lampung, 2023)
Currently, writing skill is one of the skills needed in the era of disruption like now. This is because writing is part of the human ability to meet their needs. On this basis, community service activities this time were carried out, with a focus on strengthening motivation and writing skills, especially anthology works (writing). This service activity takes the format of a presentation both in the form of technical presentation of material and motivational seminars. Presentation of the material is carried out using the lecture method, question and answer, and assignment/post test. In general, the result of this community service activity is that the activity participants have a good understanding of the material presented and have basic skills related to writing anthologies. This activity also has a social impact based on the good response given by the activity participants.Keywords: Writing, Work, Anthology, LiteracyDoi: https://dx.doi.org/10.23960/JPSI/v3i1.41-47